Comparative floral anatomy of Strobilanthinae (Acanthaceae), with particular reference to internal partitioning of the flower - Moylan, E; Rudall, P; Scotland, R (2004)
This paper provides the first comparative survey of structural variation in inflorescence architecture and flower structure of Hemigraphis and other members of the subtribe Strobilanthinae (Acanthaceae). Several discrete structural characters are identified which may provide support for phylogenetic relationships within the group. These include (1) the presence or absence of an accessory bud, (2) the presence or absence of a hollow style, (3) the presence or absence of an abscission layer, (4) the number of stamens comprising the androecium, and (5) the pattern of filament detachment. The structure of the filament curtain, a complex structure that partitions the flower, is also investigated. A more precise term for this structure "stapetal curtain" is suggested since it is a result of close synorganisation between the filaments and corolla tube. This structure appears to have a wide distribution throughout Acanthaceae and is not confined to Ruellieae s.l., as previously described. The earlier characterisation of four discrete types of filament curtain is unsatisfactory, since many of the features used to distinguish them are continuous and not unique features of particular species. © Springer-Verlag 2004.